Hutsulka Ksenya [videorecording (DVD)] - Barnych, Yaroslav; Polyanskyi. Tymur (Gagarin Media Film Company, 2020)
A beautiful musical comedy that follows one young man's journey as he experiences the true spirit of Ukraine on his search for a woman to call his wife.